2020
DOI: 10.3390/nu12051297
|View full text |Cite
|
Sign up to set email alerts
|

Water Consumption during a School Day and Children’s Short-Term Cognitive Performance: The CogniDROP Randomized Intervention Trial

Abstract: There is still little research examining the relationship between water consumption in school and specific cognitive performance. The aim of this cluster-randomized intervention CogniDROP trial was to investigate the short-term effects of drinking water during the morning on executive functions. The participants were from the 5th and 6th grade of a comprehensive school in Germany (14 classes, n = 250, 61.6% boys). The classes were randomly divided into an intervention group (an education on healthy drinking be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…Based on urine osmolality measurement, 84% of children were dehydrated (morning Uosm >800 mOsm/kgH 2 O) at the start of a school day. Drinking water had beneficial effects on memory, verbal reasoning, and vigor [ 37 ].The results of new study of Drozdowska et al suggest that a water friendly environment supports school-aged children in adequate water intake resulting in better cognitive performance, especially short-term memory [ 6 ]. In our study, 53% of all children featured an inadequate level of hydration during their stay at school, which turned out to be a risk factor of difficulties with concentration declared by students and could affect both current and long term learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on urine osmolality measurement, 84% of children were dehydrated (morning Uosm >800 mOsm/kgH 2 O) at the start of a school day. Drinking water had beneficial effects on memory, verbal reasoning, and vigor [ 37 ].The results of new study of Drozdowska et al suggest that a water friendly environment supports school-aged children in adequate water intake resulting in better cognitive performance, especially short-term memory [ 6 ]. In our study, 53% of all children featured an inadequate level of hydration during their stay at school, which turned out to be a risk factor of difficulties with concentration declared by students and could affect both current and long term learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The search identified 816 articles using the reference terms proposed, of which only 10 were selected to perform a qualitative synthesis of their content (5 randomized and 5 crossover studies). From the studies evaluated using the RoB 2 (Figures 2) 6,7,10,28,29 , 4 presented some concerns on the overall critical analysis of bias 6,7,10,28 , and one had a high risk of bias 29 . Regarding the crossover studies (Figure 3), all studies showed some concerns on the risk of bias through ROBINS-I 9,24-27 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the participants' characteristics in the selected studies, the sample was composed only of children and adolescents whose ages varied between 4 and 17. Most of the selected studies conducted their interventions within the school where they selected students at random, allocating them into two or three groups, with one being the control and the others for interventions 6,7,10,28,29 . Five studies made a single group and performed the intervention with all participants, evaluating them before and after the intervention 9,[24][25][26][27] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations